24. EVALUATE THE RESULTS OF TREATMENT OF ACUTE RESPIRATORY FAILURE IN PRETERM NEWBORNS USING SURFACTANT AT PHU THO PROVINCIAL OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluate the results of treatment of acute respiratory failure in preterm newborns using surfactant at Phu Tho Provincial Obstetrics and Pediatrics Hospital, 2022 - 2023. Study subjects: Preterm newborns with acute respiratory failure were prescribed treatment with surfactant at Phu Tho Provincial Obstetrics and Pediatrics Hospital from October 2022 to August 2023. Methods: Descriptive cross sectional study. Results: 38 preterm newborns with acute respiratory failure were treated with surfactant, of which 28 were male (accounting for 73.7%), average gestational age was 31.97 ± 2.92 weeks and average birth weight was 1973.7±738.4 grams. Before treatment, 78.9% of patients had a Silverman score >5, of which 53.3% of the early treatment group and 46.7% of the late treatment group, the most common plain chest X-ray was stage III internal membrane (47.4%), 100% of patients had PaO2/FiO2 < 300. Surfactant treatment reduced FiO2 requirements at the time after 72 hours of treatment, the mean Silverman score decreased to 3.74 in the early treatment group and 3.84 in the late treatment group. Conclusion: Treatment of acute respiratory failure in preterm newborns using surfactant showed effectiveness in improving respiratory failure of the patients.
Keywords: Acute respiratory failure, hyaline membrane, preterm newborn, surfactant.